2021
DOI: 10.3390/ijerph18030981
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Intolerance of Uncertainty and Mental Health among Back-To-School Students in Wuhan: The Moderation Effect of Social Support

Abstract: The current wave and future trend of the novel coronavirus disease 2019 (COVID-19) has triggered public uncertainty, causing unbearable psychological pressure on people. A cross-sectional online questionnaire was conducted among back-to-school students in Wuhan from 31 August 2020, to 14 September 2020, by using convenience sampling. A total of 1017 participants voluntarily provided sociodemographic characteristics and accomplished the following scales: the Intolerance of Uncertainty Scale (IUS-12), the Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 51 publications
5
50
0
2
Order By: Relevance
“…The present results emphasize the importance of strong social support to prevent mental health disorders, which has been previously demonstrated (22,30,31). Positive social support can not only buffer the effect of uncertainty and stress related to the pandemic on depressive symptoms (30,32), but also increase the feeling of social connectedness, which could protect students against depressive symptoms (12). However, never or rarely seeking help from others or having fewer supportive relatives or friends may cause students to feel less connected with others and lead to a higher level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The present results emphasize the importance of strong social support to prevent mental health disorders, which has been previously demonstrated (22,30,31). Positive social support can not only buffer the effect of uncertainty and stress related to the pandemic on depressive symptoms (30,32), but also increase the feeling of social connectedness, which could protect students against depressive symptoms (12). However, never or rarely seeking help from others or having fewer supportive relatives or friends may cause students to feel less connected with others and lead to a higher level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…After students returned to school, relevant departments should provide more academic support, such as academic guidance from teachers or trustworthy peers and lectures on learning methods or time management. Considering that the stage of epidemic prevention and control can last for a long time, colleges should regularly disclose prevention and control measures through official channels, which would be beneficial to decreasing student's feeling of uncertainty and, thus, reducing their anxiety and depression (32,62). Regarding the pressure of finding a job, the employment guidance department should carry out relevant thematic educational and consultation activities for these students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 The results of this study support the literature, which showed that informal social support from family, friends, and peers improve self‐concept and provide effective help during times of stress. 25 , 27 …”
Section: Discussionmentioning
confidence: 99%